2019
DOI: 10.3390/cells8030241
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Primary Cilia in the Crosstalk between the Ubiquitin–Proteasome System and Autophagy

Abstract: Protein degradation is a pivotal process for eukaryotic development and homeostasis. The majority of proteins are degraded by the ubiquitin–proteasome system and by autophagy. Recent studies describe a crosstalk between these two main eukaryotic degradation systems which allows for establishing a kind of safety mechanism. If one of these degradation systems is hampered, the other compensates for this defect. The mechanism behind this crosstalk is poorly understood. Novel studies suggest that primary cilia, lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 166 publications
(209 reference statements)
1
18
0
Order By: Relevance
“…Moreover, it has been previously reported that selective degradation of ciliary proteins can also be mediated by the ubiquitin-proteasome system (UPS) to control ciliogenesis and cilia maintenance [39,40]. Autophagy and UPS are, at least partially, redundant and a crosstalk exists between them concerning their role on cilia biology [40], suggesting that the mechanism/s underlying degradation of positive and negative effectors of ciliogenesis could be intricate and depending on different cell types and/or culture conditions.…”
Section: Autophagy Controls Ciliogenesis and Cilia Lengthmentioning
confidence: 99%
“…Moreover, it has been previously reported that selective degradation of ciliary proteins can also be mediated by the ubiquitin-proteasome system (UPS) to control ciliogenesis and cilia maintenance [39,40]. Autophagy and UPS are, at least partially, redundant and a crosstalk exists between them concerning their role on cilia biology [40], suggesting that the mechanism/s underlying degradation of positive and negative effectors of ciliogenesis could be intricate and depending on different cell types and/or culture conditions.…”
Section: Autophagy Controls Ciliogenesis and Cilia Lengthmentioning
confidence: 99%
“…In addition, we also found the high expression of OFD1 in CMPTs by immunohistochemistry, which is an important inhibitor of primary cilia in cancer cells ( Wiegering et al, 2019 ). The elevation of OFD1 indicates a decrease in autophagy and the disappearance of cilia, and studies have shown a close relationship between the disappearance of cilia and tumorigenesis ( Tang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 61%
“…The expression of PD-L1 (B7H1/CD274), B7H3 (CD276), and B7H4 in tissues was observed in all five patients ( Table 2 ). It is well known that PDL1, B7H3, and B7H4 are highly expressed in tumor tissues to achieve immune escape and promote tumorigenesis ( Wiegering et al, 2019 ). It is notable that PDL1, B7H3, B7H4, and other indicators are mostly expressed in mucus cells of CMPTs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multiple lines of research have revealed that autophagy (Tang et al ., 2013), the ubiquitin-proteasome system (Kasahara et al ., 2014), actin remodeling factors such as LIM kinase 2 (LIMK2), testicular protein kinase (TESK1) (Kim et al ., 2015b), and serine/threonine kinases such as intestinal cell kinase (ICK) (Chaya et al ., 2014; Moon et al ., 2014) are critical for the maintenance and function of primary cilia. More recently, among these various regulators of ciliogenesis or ciliary function, interest in the bidirectional interaction between primary cilia and autophagy is increasing (Pampliega and Cuervo, 2016; Wiegering et al ., 2019). Indeed, it has been reported that cells with defective cilia show reduced autophagy (Pampliega et al ., 2013) and dysfunction of ICK known as ciliary protein leads to perturbation of ciliary signaling and autophagy (Tong et al ., 2017), which suggests that there is a close relationship between primary cilia and autophagy.…”
Section: Primary Ciliamentioning
confidence: 99%